Lithium ion solid-state battery electrode material and preparation method thereof
By using cross-linking technology of coordination metal clusters and copolymer matrix in lithium-ion solid-state battery electrode materials, the problem of reduced conductivity and lifetime of batteries in high salt concentration and high humidity environments is solved, and higher conductivity and stability are achieved.
Patent Information
- Application Number
- CN202510189412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
When lithium-ion solid-state batteries are used in high salt concentration or high humidity environments, the interface impedance of the electrode material increases, resulting in a decrease in battery conductivity and life.
A preparation method is adopted to produce coordination metal clusters by reacting nitrogen source and carboxy-assisted ligand with metal salt solution, and crosslinking with a copolymer matrix of cellulose derivatives and functional organic groups to form a composite solution. Finally, electrode active substances are added to the lithium salt solution to prepare lithium ion solid battery electrode material.
It improves the conductivity and stability of the battery in high salt concentration and high humidity environments, extends the cycle life and conductivity efficiency of the battery, and avoids corrosion and lithium extraction problems.
Smart Images

Figure CN119674084A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium ion solid-state battery electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion solid-state batteries are lithium-ion batteries that use solid electrolytes instead of traditional liquid electrolytes. Compared with liquid batteries, solid-state batteries have higher safety, energy density and longer cycle life. The electrolyte of solid-state batteries is usually ceramic or polymer material, which can work in a wider temperature range and does not face the risk of leakage or combustion like liquid batteries.
[0003] In some special applications, lithium-ion solid-state batteries need to work in environments with high salt concentrations or high humidity. These environments pose challenges to the material properties, long-term stability, and life of the battery, so the battery is required to be able to withstand extreme conditions. For example, in marine research or seabed detection equipment, these devices include ocean depth detectors, underwater robots, seabed sensors, etc. The salt water in the marine environment is highly corrosive, and the battery must have sufficient corrosion resistance and long-term stability to continue to work in such an environment. However, in the related art, the interface between the electrode materials of the lithium-ion solid-state battery is affected by moisture or salt, resulting in an increase in the interface impedance, thereby reducing the overall conductivity of the battery, resulting in a decrease in the battery's conductive efficiency and life. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a lithium ion solid-state battery electrode material and a preparation method thereof, aiming to solve the problem of decreased battery life and conductive efficiency.
[0005] To solve the above technical problems, the present invention is implemented as follows: a method for preparing a lithium ion solid-state battery electrode material is provided, the steps comprising: S1, adding a nitrogen source and a carboxyl auxiliary ligand into a metal salt solution, and performing a thermal reaction to obtain a coordinated metal cluster; S2, mixing the cellulose derivative and the functional organic group, and performing a polymerization reaction to obtain a copolymer matrix; S3, dissolving the coordinated metal cluster and the copolymer matrix in a lithium salt solution, performing a cross-linking reaction, and obtaining a composite solution; S4, adding the electrode active material to the composite solution, stirring it evenly and degassing it, and then coating it on the current collector, and drying it to obtain the lithium ion solid-state battery electrode material.
[0006] In some embodiments of the present invention, in step S1, the nitrogen source includes at least one of imidazoline, pyridine, and ethylenediamine, the carboxyl auxiliary ligand includes at least one of carboxylic acid, oxalic acid, and acetic acid, and the metal salt solution includes at least one of copper (II) nitrate, zinc (II) nitrate, and cobalt (II) chloride.
[0007] In some embodiments of the present invention, calculated by mass ratio, the nitrogen source: the carboxyl auxiliary ligand: the metal salt solution = 1~3:1:1.
[0008] In some embodiments of the present invention, step S1 comprises: S1.1, dissolving the selected metal salt in anhydrous ethanol or water, stirring until completely dissolved, to obtain a metal salt solution; S1.2, add the nitrogen source and carboxyl auxiliary ligand to the metal salt solution, raise the temperature to 50-60°C, and stir until completely dissolved; S1.3. Raise the temperature to 70-80℃ and keep warm for 2-6h. After the end of the heat preservation, cool naturally and filter and dry to obtain the coordinated metal clusters.
[0009] In some embodiments of the present invention, step S2 includes: S2.1, dissolving the cellulose derivative in water or anhydrous ethanol, stirring with a magnetic stirrer at room temperature to ensure that the cellulose derivative is completely dissolved, to obtain a cellulose derivative solution; S2.2, adding the functional organic group solution to the cellulose solution, adding the dispersant while stirring, and stirring for 20 to 30 minutes to obtain a mixed solution; S2.3. Add an initiator to the mixed solution, carry out a polymerization reaction at a temperature of 60-80° C. for 4-6 hours. Keep stirring during the reaction. After the reaction is completed, filter to remove unreacted monomers and impurities, and obtain a copolymer matrix after drying.
[0010] In some embodiments of the present invention, in step S2, the cellulose derivative includes at least one of cellulose ether, cellulose acetate, and cellulose ester, the functional organic group includes at least one of an acrylate group, an imidazoline group, and an acrylic functional group, the dispersant includes at least one of sodium persulfate, hydrogen peroxide, and diphenyl peroxide, and the initiator includes at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and polyvinyl alcohol.
[0011] In some embodiments of the present invention, calculated by mass ratio, the functional organic group: the cellulose derivative = 1:4-10.
[0012] In some embodiments of the present invention, step S3 includes: S3.1, first dissolving the coordinated metal cluster in a solvent, stirring in a temperature-controlled stirrer to ensure that the solution is uniform, and controlling the reaction temperature at 50-70° C. to obtain a coordinated metal cluster solution, wherein the solvent comprises at least one of anhydrous ethanol, dimethylsulfamide, and N,N-dimethylformamide; S3.2, dissolving the copolymer matrix in anhydrous ethanol or acetone, using a heating stirrer to maintain the temperature between 50 and 60°C to obtain a copolymer solution, and then adding the coordinated metal cluster solution to the copolymer solution, stirring for 1 to 2 hours to obtain a composite solution.
[0013] In some embodiments of the present invention, in step S4, the electrode active material includes a positive electrode active material or a negative electrode active material, the positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, and nickel-rich ternary materials, the negative electrode active material includes at least one of graphite, silicon-based materials, and lithium metal, the current collector includes a positive electrode current collector or a negative electrode current collector, the positive electrode current collector includes at least one of aluminum foil, nickel foil, and titanium foil, and the negative electrode current collector includes at least one of copper foil, stainless steel foil, and nickel foil.
[0014] The present invention provides a lithium-ion solid-state battery electrode material, characterized in that it is prepared by the above-mentioned method for preparing a lithium-ion solid-state battery electrode material, wherein the lithium-ion solid-state battery electrode material comprises a coordination metal cluster, a copolymer matrix and a lithium salt; wherein: The coordinated metal cluster is used to enhance the conductivity, stability and interaction with lithium ions of the lithium ion solid-state battery electrode material; The copolymer matrix is used to provide structural support, enhance mechanical strength, and assist lithium ion transport; The lithium salt is used to provide a lithium ion source and promote ion conductivity.
[0015] Compared with the prior art, the method for preparing the lithium ion solid-state battery electrode material in the present invention has the following beneficial effects: The preparation process of the coordinated metal clusters is to react nitrogen sources and carboxyl auxiliary ligands with metal salt solutions, and the generated metal clusters have high stability and good electronic conductivity. These metal clusters can enhance the electronic conductivity of electrode materials and reduce the conductivity loss of batteries in high salinity and high humidity environments. In an environment with high salt concentration, the stability of the coordinated metal clusters helps prevent corrosion inside the battery, and the good conductivity enables the battery to maintain high performance in extreme environments. The copolymer matrix of cellulose derivatives and functional organic groups has excellent structural support and mechanical strength. The copolymer matrix provides a framework for the electrode material, and its structure can effectively resist the influence of moisture in a high humidity environment. The solid electrolyte obtained by cross-linking reaction is not easily affected by moisture in a high humidity environment, ensuring that the ionic conductivity of the battery is not affected by moisture. In addition, solid electrolytes generally have high electrochemical stability and salt corrosion resistance, so that the electrolyte can still maintain high conductivity and stability in a high salinity environment.
[0016] Therefore, in an environment with high salt concentration, lithium-ion solid-state battery electrode materials can avoid the corrosion or lithium precipitation problems caused by salt in common liquid batteries. The corrosion resistance of coordinated metal clusters and solid electrolytes can ensure that the battery still maintains good ionic conductivity in a high-salt environment and improve the power density and efficiency of the battery. In a high-humidity environment, solid electrolytes can effectively reduce the impact of moisture on the battery. The solid electrolyte material obtained by cross-linking reaction has good moisture isolation and mechanical stability, avoiding the problem of electrolyte degradation caused by moisture penetration, and improving the cycle life and conductivity efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic flow chart of a method for preparing a lithium-ion solid-state battery electrode material in one embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0019] Please refer to Figure 1 The present invention provides a method for preparing a lithium-ion solid-state battery electrode material, the steps comprising: S1, adding a nitrogen source and a carboxyl auxiliary ligand to a metal salt solution, performing a heat reaction, and obtaining a coordinated metal cluster. In step S1, the nitrogen source includes at least one of imidazoline, pyridine, and ethylenediamine, the carboxyl auxiliary ligand includes at least one of p-carboxylic acid, oxalic acid, and acetic acid, and the metal salt solution includes at least one of copper (II) nitrate, zinc (II) nitrate, and cobalt (II) chloride.
[0020] Calculated by mass ratio, nitrogen source: carboxyl auxiliary ligand: metal salt solution = 1~3:1:1.
[0021] Step S1 includes: S1.1. Dissolve the selected metal salt in anhydrous ethanol or water and stir until completely dissolved to obtain a metal salt solution.
[0022] By dissolving the metal salt, the metal ions are evenly distributed in the solution, laying the foundation for the subsequent coordination reaction. Anhydrous ethanol or water is a common solvent that can effectively dissolve most metal salts and has good compatibility with the dissolution of nitrogen sources and carboxyl auxiliary ligands, ensuring the smooth progress of subsequent reactions. The dissolution process helps the metal salt to form a stable coordinated metal cluster when reacting with the ligand, optimizing the release and reaction activity of the metal ions.
[0023] S1.2. Add the nitrogen source and carboxyl auxiliary ligand to the metal salt solution, heat to 50-60°C, and stir until completely dissolved.
[0024] By adding nitrogen sources (such as imidazoline, pyridine, ethylenediamine) and carboxyl auxiliary ligands (such as p-carboxylic acid, oxalic acid, acetic acid), they provide coordination sites, which help metal ions to form coordination compounds with these ligands to form stable coordinated metal clusters.
[0025] Heating the solution to 50-60°C helps accelerate the dissolution of the nitrogen source and carboxyl ligands and their coordination reaction with metal ions. Temperature control ensures a suitable reaction rate and avoids unnecessary side reactions caused by excessively high temperatures. This temperature range helps the coordination reaction of the nitrogen source and ligands with metal ions to be more rapid and complete, ensuring the formation of coordinated metal clusters.
[0026] S1.3. Raise the temperature to 70-80℃ and keep warm for 2-6h. After the end of the heat preservation, cool naturally and filter and dry to obtain the coordinated metal clusters.
[0027] Heating to 70-80°C and keeping it warm for 26 hours can promote the completion of the coordination reaction, allowing the metal ions and ligands to fully react to form stable coordinated metal clusters. This temperature range helps to increase the stability of the coordinated metal clusters and prevent adverse side reactions caused by excessively high temperatures.
[0028] The long-term heat preservation reaction ensures the complete formation of the metal clusters and helps to remove the by-products of the reaction. The filtration and drying process after cooling helps to obtain pure coordinated metal clusters, avoid unreacted substances remaining, and ensure the purity and performance of the final product. In this process, the reaction conditions (temperature, time, etc.) can regulate the particle size and morphology of the coordinated metal clusters, thereby affecting their electrochemical properties, such as improving ionic conductivity and stability.
[0029] During the heating process, the particle size of the coordinated metal clusters can be controlled by controlling the temperature. ,in is the reaction rate of the heating process, is the reaction rate constant of the heating process, is the activation energy of the heating reaction, is the gas constant, which is 8.314 J / (mol·K), is the real-time temperature. This equation shows that increasing the temperature will accelerate the reaction rate, thereby increasing the growth rate of the coordinated metal clusters. Controlling the reaction temperature can prevent the coordinated metal clusters from over-aggregating. It is the minimum energy required for a reaction to proceed. It characterizes the energy required for the reactants to overcome the reaction barrier. The higher the activation energy, the slower the rate at which the reaction rate constant increases at high temperatures. The activation energy is obtained by the Arrhenius equation, and the reaction rate constant is determined experimentally at different temperatures. , and then perform linear fitting to obtain the slope ( ), and thus calculate the activation energy .
[0030] The growth of coordinated metal clusters conforms to the nanoparticle growth theory, and its growth process is controlled by the following equation: in, is the radius of the coordinated metal cluster; is the temperature and concentration dependent reaction rate constant, is the initial concentration of the metal salt, is the concentration of metal ions during the reaction, It is the insulation time.
[0031] According to the above equation, It can be inferred that ,in, is the pre-exponential factor, is the metal salt concentration, It is the influence index of concentration, and its value can be 0.8~1. The pre-exponential factor is a constant of the reaction rate constant, which is related to the collision frequency of the reactants and the geometric arrangement of the reactants. It is an empirical constant obtained through experimental data. Its unit is usually consistent with the unit of the reaction rate and is independent of temperature. Through multiple sets of reaction rate constant data at different temperatures, the reaction rate constant and temperature are fitted using the Arrhenius equation to obtain the pre-exponential factor. For 10 5 ~10 13 , the specific value needs to be obtained through experimental data.
[0032] To simplify the model, we assume that the metal ion concentration changes little in the initial reaction. Approximately .
[0033] Therefore, the equation simplifies to: , It's time The particle size of the coordinated metal clusters is is the initial particle size, which is obtained by measuring the average coordinated metal cluster particle size in step S1.2. This equation shows that the growth rate of the coordinated metal cluster is related to the temperature. and metal salt concentration The increase in temperature will accelerate the growth of coordinated metal clusters. Too high a temperature may lead to excessive particle growth, resulting in uncontrolled particle size and the formation of larger metal clusters. This will reduce the specific surface area of the material, thereby affecting the performance of the battery, especially the conductivity and ion insertion / extraction efficiency. Higher concentrations will promote the rapid growth of coordinated metal clusters, resulting in larger particle size.
[0034] Coordination metal clusters with smaller particle sizes have higher specific surface areas, which means they can provide more active sites for lithium ions to embed and extract. A higher specific surface area usually increases the capacity of the electrode material because more lithium ions can participate in the battery's charge and discharge process. By increasing the surface area of the coordination metal clusters, the specific capacity of the electrode material can be improved.
[0035] The small particle size of the coordinated metal clusters means that they can form a more uniform conductive network. Small-sized coordinated metal clusters generally reduce barriers to electron conduction, thereby improving the electronic conductivity of electrode materials. Smaller particle sizes can help batteries perform better at high current densities because they can conduct electrons faster. Improving the electronic conductivity of electrode materials is especially advantageous during high-rate charge and discharge, reducing resistance losses in batteries during rapid charge and discharge.
[0036] Smaller coordinated metal clusters have more surface sites, and lithium ions can be inserted and removed more quickly, thereby increasing the charge and discharge rate of the battery. This is particularly important for high power density applications, such as electric vehicles and fast charging devices. Improving the charge and discharge rate of electrode materials makes them more efficient under fast charge and discharge conditions.
[0037] During the charge and discharge process, lithium ions will be embedded in and out of the electrode material, resulting in changes in the volume of the material. Small-sized coordinated metal clusters can alleviate volume expansion and reduce structural damage to electrode materials during long-term use. Compared with larger particles, smaller particles are more stable in structure and less prone to fragmentation or expansion problems. This enhances the cycle stability of the electrode material and extends the battery life.
[0038] Controlling the particle size of the coordination metal clusters helps to improve the stability of the coordination metal clusters and prevent them from agglomerating or agglomerating during the charge and discharge process. Coordination metal clusters with smaller particle sizes are usually more dispersed, reducing the loss of surface active sites and improving the long-term stability of the coordination metal clusters in the electrode material. This enhances the electrochemical stability of the battery material and reduces the capacity attenuation caused by particle aggregation during the cycle.
[0039] Small-sized coordinated metal clusters have stronger reactivity and can more easily participate in the migration and reaction of lithium ions in the battery. Therefore, the electrode material shows better reactivity and selectivity during the charge and discharge process, improving the overall efficiency of the battery. Improving the ion selectivity and reaction activity of the electrode material can improve the energy density and efficiency of the battery.
[0040] Smaller coordinated metal clusters help the material maintain good thermal stability during operation. Under high temperature conditions, smaller coordinated metal clusters are less likely to overheat or fail, thereby improving the thermal stability of the battery. Improving the thermal stability of the battery enhances the adaptability of the battery under different environmental conditions and avoids battery overheating and performance degradation.
[0041] The particle size of the coordinated metal clusters can be controlled within the range of 5 to 20 nm. This particle size range can provide a large specific surface area, thereby increasing the capacity of the electrode while ensuring the cycle stability and efficient ionic conductivity of the battery. The particle size of the coordinated metal clusters can be controlled by lowering the temperature or reducing the solubility of the metal salt solution, for example, adding an appropriate amount of solvent (such as anhydrous ethanol, dimethylsulfamide (DMSO), water, etc.) to the original metal salt solution to reduce the concentration of the metal salt. Through solvent dilution, the concentration of the metal salt can be made to meet the required range. Alternatively, by using a standardized metal salt solution of known concentration, dilute it according to the required ratio to obtain the required concentration. Alternatively, the solvent can be evaporated in a low-temperature vacuum environment. A rotary evaporator or other evaporation equipment can be used to remove the solvent. After evaporating to an appropriate volume, a solvent is added to the solution as needed to dilute it to the target concentration.
[0042] S2. Mixing the cellulose derivative and the functional organic group, and performing a polymerization reaction to obtain a copolymer matrix.
[0043] S2.1. Dissolve a cellulose derivative in water or anhydrous ethanol, and stir with a magnetic stirrer at room temperature to ensure that the cellulose derivative is completely dissolved to obtain a cellulose derivative solution; the cellulose derivative includes at least one of cellulose ether, cellulose acetate, and cellulose ester.
[0044] By dissolving the cellulose derivative, a uniform solution can be obtained. This provides a good foundation for the subsequent polymerization reaction, allowing the cellulose derivative to fully contact with the functional organic group. Continuous stirring with a magnetic stirrer at room temperature can ensure that the cellulose derivative is completely dissolved in the solution, thereby increasing its reactivity and promoting the smooth progress of subsequent reactions. Water or anhydrous ethanol as a solvent can not only effectively dissolve the cellulose derivative, but also provide a suitable environment for the subsequent reaction with the functional organic group. Anhydrous ethanol can help dissolve more hydrophobic cellulose derivatives.
[0045] S2.2, adding the functional organic group solution to the cellulose solution, adding the dispersant while stirring, stirring for 20-30 minutes, and obtaining a mixed solution, wherein the functional organic group includes at least one of an acrylate group, an imidazoline group, and an acrylic functional group, and the dispersant includes at least one of sodium persulfate, hydrogen peroxide, and diphenyl peroxide. Calculated by mass ratio, the functional organic group: cellulose derivative = 1:4-10.
[0046] Functional organic groups are added to the cellulose solution, and these groups are ensured to be uniformly dispersed in the solution. The introduction of functional groups gives the final copolymer material special functionalities such as ionic conductivity and coordination ability. By adding a dispersant, the functional groups and cellulose derivatives can be effectively dispersed, the agglomeration of polymers or groups can be avoided, and the uniformity of the reaction can be ensured. Dispersants can optimize the reaction system and improve the stability and performance of the material. Stirring for 20 to 30 minutes ensures that the functional organic groups and cellulose derivatives are fully mixed, which contributes to the uniform structure and excellent final performance of the copolymer. At the same time, the outer hydrophobic base of the functional group can block the infiltration of water vapor, and the inner layer contains nitrogen and oxygen coordination sites, which are conducive to the formation of reversible bonding with metal clusters and lithium salts, combining mechanical enhancement and ion channel provision, and improving the corrosion resistance of the electrode material.
[0047] Functional groups also include silane groups (such as methyltriethoxysilane), which can form a cross-linked network on the surface of the electrode material, helping to further enhance the structural stability of the electrode material, especially during long-term charging and discharging.
[0048] S2.3, adding an initiator to the mixed solution, carrying out a polymerization reaction at a temperature of 60-80°C for 4-6 hours, maintaining stirring during the reaction, filtering to remove unreacted monomers and impurities after the reaction is completed, and drying to obtain a copolymer matrix. The initiator includes at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and polyvinyl alcohol.
[0049] By adding an initiator, the polymerization reaction is started, the polymerization of the monomers is initiated, and a long-chain copolymer is formed. The function of the initiator is to generate free radicals or ions to promote the polymerization reaction of the monomers. The choice of initiator can control the rate and degree of polymerization of the polymerization reaction.
[0050] Carrying out the polymerization reaction at a temperature of 60-80°C can ensure that the reaction proceeds fully while avoiding the occurrence of side reactions caused by excessively high temperatures. Temperature control ensures that the structure and properties of the copolymer are optimized. After 4-6 hours of polymerization, the functional organic groups combine with the cellulose derivatives to form a copolymer, which enhances the conductivity, mechanical strength and stability of the final material.
[0051] The unreacted monomers, impurities and solvents are removed by filtration to obtain a pure copolymer matrix, ensuring its high purity and performance. The dried copolymer matrix can remove solvents and moisture, so that the final material has the desired physical form and is suitable for subsequent battery assembly.
[0052] S3, dissolving the coordinated metal clusters and the copolymer matrix in a lithium salt solution, performing a cross-linking reaction, and obtaining a composite solution.
[0053] Step S3 includes: S3.1. First, dissolve the coordinated metal cluster in a solvent, stir in a temperature-controlled stirrer to ensure that the solution is uniform, and control the reaction temperature at 50-70°C to obtain a coordinated metal cluster solution, wherein the solvent includes at least one of anhydrous ethanol, dimethylsulfamide, and N,N-dimethylformamide.
[0054] Dissolve the coordinated metal cluster in an appropriate solvent to ensure that the metal ions are fully dissolved and form a stable solution with the solvent. Dissolving the metal cluster is the basis for the smooth progress of subsequent reactions. The selection of solvents such as anhydrous ethanol, dimethylsulfamide (DMSO), and N,N-dimethylformamide (DMF) is to optimize the solubility and stability of the metal cluster. In particular, DMSO and DMF, as polar solvents, help to improve the solubility of metal salts and will not adversely affect the coordination reaction.
[0055] Stirring in a temperature-controlled stirrer and maintaining the reaction temperature in the range of 50-70°C helps to accelerate the dissolution process of the metal clusters and ensure the uniform distribution of metal ions in the solution. Too high a temperature may cause the volatilization of certain solvents or the degradation of the metal clusters, while too low a temperature may lead to incomplete dissolution. Therefore, proper temperature control is crucial to the efficiency of the reaction. By using a temperature-controlled stirrer, the uniformity of the metal cluster solution can be ensured, the metal ions are evenly distributed, precipitation or incomplete dissolution can be avoided, and the subsequent cross-linking reaction can proceed smoothly.
[0056] S3.2. Dissolve the copolymer matrix in anhydrous ethanol or acetone, use a heating stirrer to maintain the temperature between 50 and 60°C to obtain a copolymer solution, then add the coordinated metal cluster solution to the copolymer solution and stir for 1 to 2 hours to obtain a composite solution.
[0057] Dissolve the copolymer matrix in anhydrous ethanol or acetone to ensure that the copolymer can be fully dissolved and form a uniform solution. The choice of solvent can improve the solubility and reactivity of the copolymer, avoid group aggregation, and ensure a uniform reaction. Use a heated stirrer to stir the copolymer solution and keep the temperature between 50 and 60 ° C, which helps to accelerate the dissolution process of the copolymer, avoid excessive evaporation of the solution due to high temperature, and promote uniform dissolution and dispersion of the copolymer. Temperature control within this range ensures that the dissolution process proceeds smoothly without destroying the structure of the polymer.
[0058] The coordinated metal cluster solution is added to the dissolved copolymer solution, and stirring is performed to ensure that the metal clusters are fully mixed with the copolymer matrix. This step is to ensure the interaction between the metal clusters and the copolymer, thereby enhancing the structural stability and electrochemical performance of the composite material. Stirring for 1 to 2 hours helps to ensure that the coordinated metal clusters are evenly distributed in the copolymer matrix and form a good composite solution. Through this process, the interaction between the coordinated metal clusters and the copolymer matrix can be fully exerted.
[0059] S4. Add the electrode active material to the composite solution, stir it evenly and then degas it, then apply it on the current collector, and dry it to obtain the lithium-ion solid-state battery electrode material.
[0060] In step S4, the electrode active material includes a positive electrode active material or a negative electrode active material, the positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, and nickel-rich ternary materials, the negative electrode active material includes at least one of graphite, silicon-based materials, and lithium metal, the current collector includes a positive electrode current collector or a negative electrode current collector, the positive electrode current collector includes at least one of aluminum foil, nickel foil, and titanium foil, and the negative electrode current collector includes at least one of copper foil, stainless steel foil, and nickel foil.
[0061] The mass ratio of electrode active material to composite solution is usually controlled at 70~90:10~30, which is adjusted according to specific application requirements. Positive active materials are usually used in the positive electrode of the battery. These materials have high specific capacity, good electrochemical stability and long cycle life. Negative active materials are used in negative battery and have good conductivity and high cycle efficiency.
[0062] S4.1. Add the selected electrode active material to the composite solution and stir it using a magnetic stirrer with the stirring speed set to 500-1000 rpm to ensure that the active material is fully mixed with the composite solution.
[0063] S4.2. Use a vacuum degassing machine or ultrasonic degassing device for degassing. Set the vacuum pressure to 20~50kPa. Degassing is carried out at room temperature for 10~20min. After degassing, coat it on the current collector.
[0064] Coating method: Coating can be done by common methods such as blade coating, tape casting or spin coating. The coating method is usually selected according to the viscosity of the solution and the requirements of the electrode film. Blade coating: Suitable for thick film coating, commonly used in the preparation of battery electrode materials. Use a flat knife to evenly coat the composite solution on the surface of the current collector. Tape casting: Use a tape casting device to evenly coat the solution on the surface of the current collector, suitable for coating a larger area. Spin coating: Suitable for coating thinner layers, especially for high-performance batteries, commonly used in the preparation of thin-film batteries. Equipment: Commonly used equipment includes coaters, tape casting machines, and spin coaters, and the coating speed and thickness can be adjusted as needed. The film thickness after coating is usually between 50 and 100 μm. Control the coating speed and coating thickness to ensure uniform coating and avoid cracks or bubbles.
[0065] The slurry with the positive electrode active material added is coated on the positive electrode current collector, and the slurry with the negative electrode active material added is coated on the negative electrode current collector.
[0066] S4.3. Use a constant temperature oven or a vacuum drying oven for drying, the temperature is set to 50-80°C, the drying time is 4-8 hours, and after drying, the temperature is raised to 100-150°C, and the heat preservation time is 2-4 hours to obtain a lithium-ion solid-state battery electrode material. Drying is to remove the solvent, so that the electrode material forms a solid film and improves its structural stability. After drying, the coated electrode material is heat treated to improve the structural stability of the electrode material and remove residual solvent or moisture.
[0067] In the present invention, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) can also be used to characterize the coated electrode material to observe the microstructure of the electrode surface and the inside to ensure the uniformity and defect control of the material. Electrochemical impedance spectroscopy (EIS) test is performed to verify the ionic conductivity and electrochemical properties of the electrode material. The prepared electrode material is assembled with the negative electrode material and the solid electrolyte to form a lithium-ion solid-state battery. The performance, including specific capacity, cycle life, rate performance, etc., is evaluated by charge and discharge tests.
[0068] The present invention provides a lithium ion solid-state battery electrode material, which is prepared by a method for preparing a lithium ion solid-state battery electrode material. The lithium ion solid-state battery electrode material includes a coordination metal cluster, a copolymer matrix and a lithium salt; wherein: Coordinated metal clusters are used to enhance the conductivity, stability and interaction with lithium ions of lithium-ion solid-state battery electrode materials; The copolymer matrix is used to provide structural support, enhance mechanical strength, and assist in lithium ion transport; Lithium salts are used to provide a source of lithium ions and promote ionic conductivity.
[0069] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium-ion solid-state battery electrode material, characterized in that the steps include: S1, adding a nitrogen source and a carboxyl auxiliary ligand into a metal salt solution, and performing a thermal reaction to obtain a coordinated metal cluster; S2, mixing the cellulose derivative and the functional organic group, and performing a polymerization reaction to obtain a copolymer matrix; S3, dissolving the coordinated metal cluster and the copolymer matrix in a lithium salt solution, performing a cross-linking reaction, and obtaining a composite solution; S4, adding the electrode active material to the composite solution, stirring it evenly and degassing it, and then coating it on the current collector, and drying it to obtain the lithium ion solid-state battery electrode material.
2. The method for preparing a lithium-ion solid-state battery electrode material according to claim 1, characterized in that: In step S1, the nitrogen source includes at least one of imidazoline, pyridine, and ethylenediamine, the carboxyl auxiliary ligand includes at least one of carboxylic acid, oxalic acid, and acetic acid, and the metal salt solution includes at least one of copper (II) nitrate, zinc (II) nitrate, and cobalt (II) chloride.
3. The method for preparing a lithium-ion solid-state battery electrode material according to claim 2, characterized in that: Calculated by mass ratio, the nitrogen source: the carboxyl auxiliary ligand: the metal salt solution = 1~3:1:
1.
4. The method for preparing a lithium-ion solid-state battery electrode material according to claim 1, characterized in that: The step S1 comprises: S1.1, dissolving the selected metal salt in anhydrous ethanol or water, stirring until completely dissolved, to obtain a metal salt solution; S1.2, add the nitrogen source and carboxyl auxiliary ligand to the metal salt solution, raise the temperature to 50-60°C, and stir until completely dissolved; S1.
3. Raise the temperature to 70-80℃ and keep warm for 2-6h. After the end of the heat preservation, cool naturally and filter and dry to obtain the coordinated metal clusters.
5. The method for preparing a lithium-ion solid-state battery electrode material according to claim 1, characterized in that: The step S2 comprises: S2.1, dissolving the cellulose derivative in water or anhydrous ethanol, stirring with a magnetic stirrer at room temperature to ensure that the cellulose derivative is completely dissolved, to obtain a cellulose derivative solution; S2.2, adding the functional organic group solution to the cellulose solution, adding the dispersant while stirring, and stirring for 20 to 30 minutes to obtain a mixed solution; S2.
3. Add an initiator to the mixed solution, carry out a polymerization reaction at a temperature of 60-80° C. for 4-6 hours. Keep stirring during the reaction. After the reaction is completed, filter to remove unreacted monomers and impurities, and obtain a copolymer matrix after drying.
6. The method for preparing a lithium-ion solid-state battery electrode material according to claim 5, characterized in that: In step S2, the cellulose derivative includes at least one of cellulose ether, cellulose acetate, and cellulose ester, the functional organic group includes at least one of an acrylate group, an imidazoline group, and an acrylic functional group, the dispersant includes at least one of sodium persulfate, hydrogen peroxide, and diphenyl peroxide, and the initiator includes at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and polyvinyl alcohol.
7. The method for preparing a lithium ion solid-state battery electrode material according to claim 5 or 6, characterized in that: Calculated by mass ratio, the functional organic group: the cellulose derivative = 1:4-10.
8. The method for preparing a lithium-ion solid-state battery electrode material according to claim 1, characterized in that: The step S3 comprises: S3.1, first dissolving the coordinated metal cluster in a solvent, stirring in a temperature-controlled stirrer to ensure that the solution is uniform, and controlling the reaction temperature at 50-70° C. to obtain a coordinated metal cluster solution, wherein the solvent comprises at least one of anhydrous ethanol, dimethylsulfamide, and N,N-dimethylformamide; S3.2, dissolving the copolymer matrix in anhydrous ethanol or acetone, using a heating stirrer to maintain the temperature between 50 and 60°C to obtain a copolymer solution, and then adding the coordinated metal cluster solution to the copolymer solution, stirring for 1 to 2 hours to obtain a composite solution.
9. The method for preparing a lithium-ion solid-state battery electrode material according to claim 1, characterized in that: In step S4, the electrode active material includes a positive electrode active material or a negative electrode active material, the positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, and nickel-rich ternary materials, the negative electrode active material includes at least one of graphite, silicon-based materials, and lithium metal, the current collector includes a positive electrode current collector or a negative electrode current collector, the positive electrode current collector includes at least one of aluminum foil, nickel foil, and titanium foil, and the negative electrode current collector includes at least one of copper foil, stainless steel foil, and nickel foil.
10. A lithium-ion solid-state battery electrode material, characterized in that: It is made by the preparation method of a lithium ion solid-state battery electrode material according to any one of claims 1 to 9, wherein the lithium ion solid-state battery electrode material comprises a coordination metal cluster, a copolymer matrix and a lithium salt; wherein The coordinated metal cluster is used to enhance the conductivity, stability and interaction with lithium ions of the lithium ion solid-state battery electrode material; The copolymer matrix is used to provide structural support, enhance mechanical strength, and assist lithium ion transport; The lithium salt is used to provide a lithium ion source and promote ion conductivity.
Citation Information
Patent Citations
Positive electrode active material, positive electrode plate and lithium ion secondary battery
CN112447968A
Preparation and application of MOFs material modified lithium iron phosphate positive electrode material
CN114291802A
Binder for lithium secondary battery electrode, lithium secondary battery positive electrode comprising same, and lithium secondary battery
US20220209237A1